The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.9790/2380-07523140
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Carob (Ceratonia siliqua L.) Propagation

Abstract: Carob (Ceratonia siliqua L.) is an environmentally and economically important tree and is among the most difficult to propagate fruit species. In this study, efforts were made to propagate the plant by using three different methods; seeds germination, cuttings and micropropagation. Seeds and cuttings were scarified and disinfected under aseptic conditions to improve the germination percentage and the percentage of success of cuttings in April and September through two successive seasons (2011 and 2012). Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…Our results confirm that carob seeds gave the highest percentage of germination after 96% sulphuric acid treatment for 20 min (Zaen El Deen et al 2014) and in a shorter time as compared to hot water treatment. The almost complete germination obtained in all genotypes confirms that their embryos are ready to germinate, and that dormancy overcoming determined by the acid is associated to the almost complete disruption of the hard seed coat.…”
Section: Discussionsupporting
confidence: 84%
“…Our results confirm that carob seeds gave the highest percentage of germination after 96% sulphuric acid treatment for 20 min (Zaen El Deen et al 2014) and in a shorter time as compared to hot water treatment. The almost complete germination obtained in all genotypes confirms that their embryos are ready to germinate, and that dormancy overcoming determined by the acid is associated to the almost complete disruption of the hard seed coat.…”
Section: Discussionsupporting
confidence: 84%
“…The seed coat is rigid and incapable of absorbing water, implying that carob has challenges with natural regeneration. Consequently, carob seed germination is difficult without seed coat scarification [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, carob seeds are difficult to germinate. The seed coat is extremely hard and not ready to absorb water, so carob seeds need pre-sowing treatments (Zaen El Deen et al, 2014). Propagation by cutting is problematic because carob has been described as one of the most difficult to root species (Hartmann et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Only a small number of layers can be produced from a parent plant than when the same plant is used as source of cuttings or scions, however this method is laborious, cumbersome and expensive. Zaen El Deen et al (2014) proved that carob micropropagtion needs further studies to overcome the difficulties in the root induction. Also, El Bouzdoudi et al (2017) reported that carob can be cultured in vitro with a survival rate of 40%.…”
Section: Introductionmentioning
confidence: 99%